2020
DOI: 10.1155/2020/9267972
|View full text |Cite
|
Sign up to set email alerts
|

Lymph Node Metastases of Medullary Thyroid Cancer: Role of Calcitonin in the Washout Fluid of Fine-Needle Aspiration

Abstract: Introduction. The diagnostic value of calcitonin (CT) measurement in fine-needle aspirate washout (FNA-CT) for medullary thyroid cancer (MTC) lymph node (LN) metastases remains to be determined. It may increase the diagnostic sensitivity, but data on this subject is sparse. Objective. Our study aimed to evaluate the utility of FNA-CT in the diagnosis of LN metastases of MTC. Methods. We retrospectively investigated, in our institutional database, 69 consecutive FNA LN cytology from 42 patients who underwent FN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…As showed by our sub-analysis, the pooled sensitivity of FNA-cytology was negatively influenced by its poor performance in prospective studies; this corroborates that the cytological diagnosis of MTC during the clinical practice is more difficult than its detection when reviewing the cytological specimens for research purpose. Furthermore, the FNA-cytology sensitivity of the most recent studies [ 15 , 16 ] was improved with respect that of the previously published ones; we can speculate that cytopathologists have recently become more aware of this difficult diagnosis and, maybe, have been positively influenced by the concomitant use of FNA-CT. In addition, one study [ 12 ] showed a very poor sensitivity of cytology; this finding might be due to several reasons such as the prospective enrollment of cases and the potential difficult sampling in small nodules (i.e., median size 9.5 mm).…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…As showed by our sub-analysis, the pooled sensitivity of FNA-cytology was negatively influenced by its poor performance in prospective studies; this corroborates that the cytological diagnosis of MTC during the clinical practice is more difficult than its detection when reviewing the cytological specimens for research purpose. Furthermore, the FNA-cytology sensitivity of the most recent studies [ 15 , 16 ] was improved with respect that of the previously published ones; we can speculate that cytopathologists have recently become more aware of this difficult diagnosis and, maybe, have been positively influenced by the concomitant use of FNA-CT. In addition, one study [ 12 ] showed a very poor sensitivity of cytology; this finding might be due to several reasons such as the prospective enrollment of cases and the potential difficult sampling in small nodules (i.e., median size 9.5 mm).…”
Section: Discussionmentioning
confidence: 75%
“…The sensitivity of both FNA-cytology and FNA-CT was reported in all six studies. In addition, some of them [ 14 , 15 ] also calculated the sensitivity of FNA-CT/serum CT ratio. Table 2 illustrates the FNA results recorded in the six studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the detection of MTC, however, FNA sensitivity was only 56.4% in a pooled metanalysis of 15 studies encompassing 641 MTC lesions [13]. More recent studies also show varying sensitivities up to 86% (Table 4) [13,[43][44][45]. In a retrospective review of 61 cases, 16.4% of samples reported low cellularity of the specimen as a limiting factor [43].…”
Section: Fine Needle Aspirationmentioning
confidence: 98%